Zmiany w ukraińskim systemie partyjnym w kontekście agresji Federacji Rosyjskiej wobec Ukrainy - Pietnoczka, Paweł (Przegląd Wschodnioeuropejski, 2026)
The commencement of Russia’s aggression against Ukraine significantly affected changes in the Ukrainian party system. The previously influential political parties, namely the Party of Regions and the Communist Party of Ukraine, ceased to play any role in it. In addition, the process of outlawing pro-Russian parties was initiated, which accelerated substantially with Russia’s launch of a full-scale war in 2022. Among others, the Opposition Platform – For Life, which had the status of a parliamentary party at the time, was banned. At the same time, the aggression of the Russian Federation against Ukraine contributed to the domination of the Ukrainian political scene by pro-Western parties.